Synthesis and characterization of Sr0.5Zn0.5Mn2O4 powder for highly efficient visible light photocatalysis - Benyahia Khawla; Badaoui Mohamed; Sehil Hafida; Chougui Abdelkader; Mourad Abdel-Hamid I.; Grira Soumaya; Dehbi Abdelkader (Processing and Application of Ceramics, 2025)
Spinel oxide Sr0.5Zn0.5Mn2O4 powder was successfully synthesized using the ultrasonic process. A comprehensive characterization was conducted employing various analytical techniques, including X-ray diffraction (XRD), infrared spectroscopy (IR), UV-Vis spectroscopy, scanning electron microscopy (SEM), thermogravimetric analysis, energy-dispersive X-ray spectroscopy and point of zero charge measurements. The results of IR analysis confirmed the presence of Zn-O, Sr-O and Mn-O bonds, which are crucial for the structural integrity of the material. The XRD patterns showed enhanced crystallinity, while the band gap energy was determined to be 2.5 eV, as corroborated by UV-Vis spectroscopy. Additionally, the SEM analysis revealed that the particles exhibited uniformity in both size and shape, which is essential for consistent photocatalytic performance. Furthermore, the Sr0.5Zn0.5Mn2O4 was evaluated for its photocatalytic activity, specifically targeting the degradation of Congo red dye under visible light irradiation. The findings of the photocatalytic study demonstrated a significant improvement in degradation efficiency (99.37%), highlighting the potential application of Sr0.5Zn0.5Mn2O4 in environmental remediation. A detailed study on the influence of various parameters, including pH, the amount of catalyst and the initial concentration of dye was also conducted to optimize the photocatalytic process.